(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
Foreign Investment (PMA) is one element that plays an important role as a source of state investment. FDI is becoming more important and is considered a catalyst for economic development, a source of transfer of technology and innovation from developed to developing countries. This study aims to examine the relationship between FDI and GDP in Indonesia. The analysis tool used is the cointegration test to determine the long-term relationship between FDI and GDP, and the causality relationship between FDI and GDP using the Granger causality (GC) test which is based on VECM. This study uses data on FDI, GDP, and labour with a panel data approach from 33 provinces in Indonesia for the period 2010 - 2020. The results of the study did not show a causal relationship between FDI and GDP, labour in Indonesia. From the results of the Impulse response from the VAR, it tends to diverge, the FDI response to GDP and labour is quite good. This shows that FDI brings externalities from technological innovation, increasing the ability of the workforce requires time for learning. The ability of human resources and the absorption capacity of local companies will affect the transfer of technology brought by FDI.